ANALISIS PENGARUH LINGKUNGAN KERJA, DISIPLIN KERJA, DAN MOTIVASI KERJA TERHADAP KINERJA PEGAWAI DI DINAS PEKERJAAN UMUM DAN PENATAAN RUANG DAERAH PROVINSI SULAWESI UTARA - Dicky Fernando Rotto (Universitas Sam Ratulangi, 2022)
Abstract: This study aims to determine and analyze the effect of work environment, work discipline, and work motivation on employee performance at the Department of Public Works and Regional Spatial Planning, North Sulawesi Province. This study uses an analytical approach classified into quantitative methods. The population of this study were all employees of the Office of Public Works and Regional Spatial Planning of North Sulawesi Province, amounting to 272 people and the number of samples used after rounding up was = 73 employees. Data were obtained through the distribution of questionnaires and literature study. The analysis in this study uses multiple regression analysis. The results of the research on the F test indicate that the work environment, work discipline, and work motivation simultaneously have an effect on employee performance with a calculated F value of 14,800 with a significance of 0.000 <0.05. While the results of the T test show that the work environment variable does not partially affect employee performance with a T count value of 1.933 < T table 1.9949. Then the work discipline variable has no effect on employee performance partially with a T arithmetic value of 0.509 < T table 1.9949. Then the work motivation variable has a positive effect on employee performance partially with a T arithmetic value of 4.029 > T table 1.9949..